Microkinetic Analysis of the Oxygen Evolution Performance at Different Stages of Iridium Oxide Degradation - Geppert, Janis; Roese, Philipp; Czioska, Steffen; Escalera-Lopez, Daniel; Boubnov, Alexey; Saraci, Erisa; Cherevko, Serhiy; Grunwaldt, Jan-Dierk; Krewer, Ulrike (Journal of the American Chemical Society, 2022)
The microkinetics of the electrocatalytic oxygen evolution reaction substantially determines the performance in proton-exchange membrane water electrolysis. State-of-the-art nanoparticulated rutile IrO2 electrocatalysts present an excellent trade-off between activity and stability due to the efficient formation of intermediate surface species. To reveal and analyze the interaction of individual surface processes, a detailed dynamic microkinetic model approach is established and validated using cyclic voltammetry. We show that the interaction of three different processes, which are the adsorption of water, one potential-driven deprotonation step, and the detachment of oxygen, limits the overall reaction turnover. During the reaction, the active IrO2 surface is covered mainly by *O, *OOH, and *OO adsorbed species with a share dependent on the applied potential and of 44, 28, and 20% at an overpotential of 350 mV, respectively. In contrast to state-of-the-art calculations of ideal catalyst surfaces, this novel model-based methodology allows for experimental identification of the microkinetics as well as thermodynamic energy values of real pristine and degraded nanoparticles. We show that the loss in electrocatalytic activity during degradation is correlated to an increase in the activation energy of deprotonation processes, whereas reaction energies were marginally affected. As the effect of electrolyte-related parameters does not cause such a decrease, the model-based analysis demonstrates that material changes trigger the performance loss. These insights into the degradation of IrO2 and its effect on the surface processes provide the basis for a deeper understanding of degrading active sites for the optimization of the oxygen evolution performance.
CRIS-Team Scopus Importer:2022-08-12